Water security and management of water resources - National Workshop-cum-Seminar on "Water Security and Management of Water Resources" (2004 : Calcutta, India); Saha, Gopi Nath; India. Ministry of Science and Technology. Department of Science and Technology. National Atlas and Thematic Mapping Organisation (Kolkata : National Atlas and Thematic Mapping Organisation, Department of Science and Technology, Ministry of Science and Technology, Government of India, 2004)
Contributed articles presented at the National Workshop-cum-Seminar on Water Security and Management of Water Resources held on 23rd February, 2004 at Calcutta, India with reference to water resources development in India.
Includes bibliographical references
Keywords: Water resources development -- India; Water use -- India; Water quality management -- India